The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.31729/jnma.564
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bacteria Isolated From Urinary Tra Infection and Their Sensitivity Pattern

Abstract: A retrospective study was conducted among out-patient and in-patient in Kathmandu medical collegeTeaching hospital of one month from the duration 2060-11-15 to 2060-12 -15. Mid-stream urine [MSU] of300 patient were cultured. Out of these, 75 patients’ urine were found to have significant bacterial growth.Total of five species of bacterial species isolated were viz.E.coli 37(33.3%), Proteus species 25(27.7%),Klebsiella species 15(16.6%), Staphylococcus aureus 8(8.8%) and Pseudomonas aureginosa 1(1.1%).Regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
2
15
1
Order By: Relevance
“…coli was the most common organism isolated (64.66%) in our study which is consistent with fi ndings of previous literature of 62.88% 14 and 67.5% 15 and some studies also reported higher incidence of E. coli 87 % and 92% respectively in their study 17,18 . Klebsiella isolated (12.78%) in present study is lower than other studies where incidence varied from 15.7 to 22% 12,15,19,20 .…”
Section: Discussioncontrasting
confidence: 75%
“…coli was the most common organism isolated (64.66%) in our study which is consistent with fi ndings of previous literature of 62.88% 14 and 67.5% 15 and some studies also reported higher incidence of E. coli 87 % and 92% respectively in their study 17,18 . Klebsiella isolated (12.78%) in present study is lower than other studies where incidence varied from 15.7 to 22% 12,15,19,20 .…”
Section: Discussioncontrasting
confidence: 75%
“…As a result this study was confined to 100 adult patients (21.8%) with ages ranged between 18-75 years old (mean ± SD  44± 15.244). The low rate of growth positivity which is also observed by other researchers [16,17] may due to the presence of either slow growing organisms or organisms that cannot be grow on the ordinary media. There were 76 females and 24 males.…”
Section: Resultssupporting
confidence: 62%
“…Previous studies also reported low prevalence of UTI. 3,10,18 Low positivity might be due to the urine samples obtained from the patients from under treatment cases. The slow growing organisms and infection from them cannot able to grow on the routinely used media.…”
Section: Discussionmentioning
confidence: 99%
“…They are always vulnerable to infections by various organisms. 10 Microbial resistance to nearly all classes of antimicrobials continues to rise despite increasing awareness and concern worldwide. 11 In Nepal, Isolated pathogen frequency and antimicrobial resistant rates can vary dramatically even within the same nation.…”
Section: Urinary Tract Infections and Antibiotic Susceptibility Amongmentioning
confidence: 99%